"I could see, in the depth of his eyes, my own beauty reflected": Women's assortative preference for narcissistic, but not for Machiavellian or psychopathic male faces. (July 2016) - Lyons, Minna; Blanchard, Alyson
Abstract: Few studies have looked at assortative mating for the Dark Triad (i.e., Machiavellianism, psychopathy and narcissism), or assortative mating for facial characteristics related to personality. In two studies ( n ' s  = 302 and 262), we investigated whether women scoring high in the Dark Triad exhibited a preference for high and low Dark Triad male composite faces. In Study 1, using a two alternative forced-choice task and a short Dark Triad scale, there was little evidence for assortative mating. In Study 2, utilising a rating scale, longer personality measures, and controlling for perceptions of aggression, masculinity and dominance, we found positive assortative mating for narcissism in long-term relationships. Findings are discussed from evolutionary psychological perspective. Highlights: We investigated assortative mating for the Dark Triad facial morphs in women. This was examined across short-term and long-term mating contexts. Facial morphs were also measured for aggressiveness, dominance and masculinity. We found assortative mating for narcissism in long-term relationships.